Perlindungan Hukum Terhadap Konsumen Dalam Kegiatan Transaksi Elektronik (E-Commerce): Perspektif Undang-Undang Perlindungan Konsumen - Tamaela, Kurniawan Willem; Solichin, Rizky Amalia (PT Elaborium Elevasi Indonesia, 2025)
This study aims to determine the form of legal protection for consumers in electronic transaction activities (e-commerce) and to find out how consumer dispute resolution in conducting electronic transaction activities (e-commerce). This journal uses a normative study method with normative legal assessment techniques, where research is based on legislation and library materials related to legal issues. This research also applies a statutory approach and a conceptual approach. This research can be concluded as follows: First, the protection for consumers has basically been regulated in Law Number 8 Year 1999 on Consumer Protection (UUPK). However, the existing legal protection regulations have not been able to protect consumers in cross-border e-commerce transactions in Indonesia. Legal protection of consumer rights in electronic transactions cannot rely on one aspect of the law alone, but must involve a system of legal instruments capable of providing simultaneous and comprehensive protection. Therefore, although electronic transaction trading provides many positive impacts, there are also many negative impacts that arise. This is where the importance of regulations in the field of information technology to provide legal protection for consumers in electronic transactions such as Law No. 11/2008 on Electronic Information and Transactions and Government Regulation No. 82/2018 on the Implementation of Electronic Systems and Transactions. Second, consumer dispute resolution in e-commerce transactions has become an important issue in the growing digital era. With the existence of various regulations such as GCPL, ITE Law, and PMSE Regulation, consumers in Indonesia have received adequate legal protection in online transaction activities. Various dispute resolution mechanisms, both through litigation and non-litigation channels, as well as the existence of an internal resolution platform from e-commerce, allow consumers to claim their rights if a problem occurs.